#TITLE_ALTERNATIVE# - APRIYANTI (NIM : 23106015); Pembimbing Utama : Dr. Ir. Prihadi Setyo Darmanto, VIVI
The cement manufacturing industry using an ILC-SLC preheater configuration is a complex design. To improve its performance, knowledge is needed about mass and heat balance of the whole unit and separately for each part. In fact, to evaluate mass and heat balance of a cyclone the efficiency of the cyclone is required. Unfortunetly, direct measurement to ascertain cyclone efficiency, especially in three units cyclone below the top cyclone of each string is possible. Development of a mathematical model for clinker production based on equations of mass and heat conservation were urgently required to solve this problem, and simultaneously it was expected that it could be used for calculating the efficiency of separating materials in cyclone. This research was intended to solve these problems, which were experienced by the cement industry’s designers and practitioners. Through this research a mathematical model has been developed for clinker production involving two string ILC and SLC with a specific configuration based on conservation of mass and heat in the main equipment. In this configuration, eighteen linear equations were obtained in which eighteen parameters were unknown. Naive Gauss Elimination method was used to solve the linear equations. The results of these calculations can be used directly to determine efficiency of separating material of cyclones below the top cyclone at each string. A program was created to facilitate solving the equation. Validation with operation’s data of a cement industry in Indonesia has shown a suitability, and efficiency of separating materials in cyclones can be calculated with acceptable value. Thus, the mathematical models of clinker production developed in this research are expected to be able to be used as a tool for the cement industry’s designers and practitioners in improving overall performance of the cement industry.